2019
DOI: 10.1002/cssc.201900799
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Borrowing Hydrogen C‐Alkylation of Oxindoles with Alcohols

Abstract: A general and efficient iron‐catalyzed C‐alkylation of oxindoles has been developed. This borrowing hydrogen approach employing a (cyclopentadienone)iron carbonyl complex (2 mol %) exhibited a broad reaction scope, allowing benzylic and simple primary and secondary aliphatic alcohols to be employed as alkylating agents. A variety of oxindoles underwent selective mono‐C3‐alkylation in good‐to‐excellent isolated yields (28 examples, 50–92 % yield, 79 % average yield).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 102 publications
(14 reference statements)
1
37
0
Order By: Relevance
“…HB methylation of 2‐oxindoles and indoles reported by Morrill (A), indole alkylation reported by Renaud and co‐workers (B), and alkylation of 2‐oxindole reported by Morrill (C) …”
Section: Applications In Reactions Involving Ht Stepsmentioning
confidence: 91%
See 1 more Smart Citation
“…HB methylation of 2‐oxindoles and indoles reported by Morrill (A), indole alkylation reported by Renaud and co‐workers (B), and alkylation of 2‐oxindole reported by Morrill (C) …”
Section: Applications In Reactions Involving Ht Stepsmentioning
confidence: 91%
“…A more thorough study on indole alkylation was simultaneously reported by Renaud and co‐workers using pre‐catalysts 1f and 5fa (Scheme B): a series of benzylic as well as aliphatic alcohols were employed as alkylating agents. Very recently, Morrill and co‐workers extended the scope of oxindole alkylation to several different 2‐oxindoles and to a number of benzylic and aliphatic alcohols (Scheme C) …”
Section: Applications In Reactions Involving Ht Stepsmentioning
confidence: 99%
“…I-V (Moulin et al, 2013) and cat. VI (Dambatta et al, 2019) were prepared according to the literature. All commercially available reagents and solvents (purchased from Sigma-Aldrich, TCI, Alfa-Aesar and Acros) were used without further purification unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, we introduced in catalysis the tricarbonyl iron complex Fe2 bearing a diaminocyclopentadienone ligand [21]. Compared to other cyclopentadienone iron carbonyl complexes, this phosphine-free iron complex has, to the best of our knowledge, the highest catalytic activities to date in reductive amination [21], in chemoselective reduction of α,β-unsaturated ketones [22], in the hydrogenation of carbon dioxide [23], in alkylation of ketones [24][25][26][27], amines [25,28], oxindoles [29], indoles [25,30] and alcohols [31,32]. In our ongoing interest in reduction and alkylation, we thought that a water-soluble analog of Fe2 would be more active than our previous water-soluble cyclopentadienone iron complex Fe3 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%